Formal Techniques for Networked and Distributed Systems: FORTE 2001 IFIP TC6/WG6.1 — 21st International Conference on Formal Techniques for Networked and Distributed Systems August 28–31, 2001, Cheju Island, Korea - Kim, Myungchul; Chin, Byoungmoon; Kang, Sungwon; Lee, Danhyung (Formal techniques for networked and distributed systems : FORTE 2001 : IFIP TC6 WG6.1--21st International Conference on Formal Techniques for Networked and Distributed Systems, August 28-31, 2001, Cheju Island, Korea, 2001)
FORTE 2001, formerly FORTE/PSTV conference, is a combined conference of FORTE (Formal Description Techniques for Distributed Systems and Communication Protocols) and PSTV (Protocol Specification, Testing and Verification) conferences. This year the conference has a new name FORTE (Formal Techniques for Networked and Distributed Systems). The previous FORTE began in 1989 and the PSTV conference in 1981. Therefore the new FORTE conference actually has a long history of 21 years. The purpose of this conference is to introduce theories and formal techniques applicable to various engineering stages of networked and distributed systems and to share applications and experiences of them. This FORTE 2001 conference proceedings contains 24 refereed papers and 4 invited papers on the subjects. We regret that many good papers submitted could not be published in this volume due to the lack of space. FORTE 2001 was organized under the auspices of IFIP WG 6.1 by Information and Communications University of Korea. It was financially supported by Ministry of Information and Communication of Korea. We would like to thank every author who submitted a paper to FORTE 2001 and thank the reviewers who generously spent their time on reviewing. Special thanks are due to the reviewers who kindly conducted additional reviews for rigorous review process within a very short time frame. We would like to thank Prof. Guy Leduc, the chairman of IFIP WG 6.1, who made valuable suggestions and shared his experiences for conference organization.